MARS/NDRI/KSU Communications Workshop: Part 3. Dhulikhel Conference Responses Distributed to Workshop Participants - Leslie, John F.; Harvey, Jagger J.W.; Morris, Jeffery B. (My University, 2022)
A. Day 1 – Consumers (Pages 1-8) B. Day 1 – Producers, Traders Distributors (Pages 9-26) C. Day 1 – Health Professionals (Pages 27-31) D. Day 1 – Educators, Trainers & Researchers (Pages 32-43) E. Day 1 – Policy Makers & Regulators (Pages 44-59) F. Day 2 – Communication Considerations (Pages 60-62)
Keywords: Aflatoxin; Food Safety; Mycotoxins; Nepal; Public Health; Risk Communication